(untitled) (Al-Qamar, 2021)
Tradition of Na;at in Urdu, from view point of diction and style, is very dynamic especially in the Rands of women this tradition meets novel standards of tone, rythim and phraseology tinged in modern expressions of dominant effect. Multiple aspects covering. The Holy traits of Rasoolullah (PBUH) mirrod excellently in the genre of Na’at by woman writers is the crux of this article.